Manajemen Strategi dalam Meningkatkan Pendapatan Asli Daerah Provinsi Kepulauan Riau(Studi pada Bea Balik Nama Kendaraan Bermotor (BBN-KB) di Kantor Unit Pelaksana Teknis Daerah Pelayanan Pajak Daerah (UPTD PPD) Kijang) - Herlina, Vera; Didik Gunawan Suharto; Elisa Susanti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze management strategies to increase Regional Original Revenue (PAD) in the Riau Islands Province through the Motor Vehicle Transfer Fee (BBN-KB) sector at the Kijang Regional Tax Service Technical Implementation Unit (UPTD PPD). The research method used was a qualitative method with a descriptive approach. Data were obtained through in-depth interviews, observation, and documentation with key informants, including officials and employees of the Riau Islands Province Regional Tax and Retribution Management Agency (BP2RD). The results indicate that the implemented management strategy encompasses four main components: the external environment, the internal environment, strategy formulation, and strategy implementation. External factors such as local government support, cross-agency collaboration, and the use of information technology contributed positively to the increase in PAD revenue from the BBN-KB sector. However, internal constraints remain, such as the limited number of tax assessment officers, which impacts service effectiveness and the length of the tax administration process. The conclusions of this study indicate that the implementation of strategic management at the Kijang PPD UPTD has been effective and in accordance with strategic management principles. However, improvements in human resource quality and strengthening of the digital service system are needed to ensure optimal and sustainable implementation of the strategy. Keywords: Strategic Management, Locally-Owned Revenue, Local Taxes, Kijang PPD UPTD